The plasmonic effect of gold nanorods on charged molecules: SERRS and SEF effects - Oliveira, Tatiana Aparecida [UNESP]; Rubira, Rafael Jesus Gonçalves [UNESP]; Da Silva Martin, Cibely [UNESP]; De Barros, Anerise; Mazali, Italo Odone; Constantino, Carlos José Leopoldo [UNESP] (FapUNIFESP (SciELO), 2021)
Target molecules adsorbed onto metallic nanoparticles can have their Raman and/or fluorescence signals enhanced, leading to the called surface-enhanced [resonance] Raman scattering (SE[R]RS) or surface-enhanced fluorescence (SEF). Here we have applied Au nanorods (AuNRs) coated with a surfactant bilayer leading to a positive surface charge to investigate the role played by these AuNRs in colloidal suspension on SERRS and SEF effects of charged molecules. In the case of the anionic nickel (II) tetrasulfonated phthalocyanine (NiTsPc), besides achieving SERRS with an enhancement factor (EF) of ca. 105, the AuNRs allowed the analytical application of the SERRS effect for the NiTsPc between 8.3x10-6 and 4.0x10-5 mol L-1. The limit of detection of 4.8x10-7 mol L-1 (at 752 cm-1) and 1.3x10-6 mol L-1 (at 1338 cm-1) was found. In the case of the cationic methylene blue, the SEF effect was achieved reaching an EF of ca. 10. Besides, fundamental discussions are carried out considering the results presented here.
Keywords: Charge effect; Gold nanorods; SEF; SERRS